Entomophagy: a preliminary study on the perception of students of Animal Science and Veterinary Medicine in Brazil (Research, Society and Development, 2023)
The research aims to prospect information related to the perception of students of Animal Science and Veterinary Medicine in Brazil regarding the use and acceptance of insects and their by-products in animal and human food. A study was conducted based on objective questions in an online form designed to collect the necessary data, classified as a descriptive exploratory cross-sectional study on the subject. A total of 432 answers were distributed among the regions of Brazil, namely: Northeast (68.4%), Southeast (12.8%), South (11.4%), North (4.4%) and Midwest (3%). The results show that 76.9% of the students know about the use of insects in human and animal food, but only 48.1% would recommend insect-based feeding. Even with 84.3% not having entomophobia and knowing about entomophagy, only 30.1% would ingest a bread made from insect flour, and would recommend to other people the consumption of this type of ingredient. Finally, it is pertinent to infer that the use of insects in human and animal food, despite being known by this sample group, is still superficial and with several paradigms, which make their effective use impossible. It is suggested that entomophagy be included in the curricular projects of Animal Science and Veterinary Medicine courses, so that this knowledge can really be a viable alternative for the production of alternative protein in Brazil.